Metallic anion recovery from aqueous streams and removal agent recycle in the polymer–surfactant aggregate process - Shen, L; Hankins, N (Elsevier, 2016)
In a previous contribution, a new application of the polymer–surfactant aggregate (PSA) process was developed; the removal of metallic anions from dilute aqueous solutions. A subsequent pH adjustment method has been developed to recover the metallic anions from the flocculated PSAs into a concentrated solution and then to recover the polymer (PAA) and surfactant (MTAB) for recycling. The PSA is a colloidal structure that is formed by micelle-like aggregates associating with the oppositely charged polymer chains. The PSA can then bind with metallic anions, and will eventually flocculate out of the solution under colloidal destabilisation. In the work presented, a small volume of 0.1 M NaOH is firstly added to the flocs to leach out the bound metallic anions in 15 min, and then a coarse filter is used to separate out the basic solution containing 5–20 times more concentrated metallic anions than the original effluent. After the metallic anion recovery, the flocs can be completely dissolved in a small volume of 0.05 M H 2 SO 4 . This acidic solution, containing PAA and MTAB, is then reused in the next treatment cycle; meanwhile, the pH of the feed is adjusted to 5.3 by adding NaOH. The results show that the recovery efficiency of CrO 4 2 − at an optimum pH of 12 is 94%, and the recovery efficiency of PAA–MTAB at its optimum pH of 1.4 is 94%. The kinetics of the recovery process is quick; both the basification and acidification steps can be completed within 15–20 min. In addition, the removal efficiency of 0.2 mM CrO 4 2 − solution remains at the same level when using previously recycled PAA and MTAB (with a small makeup of the MTAB to cover leakage at the metallic anion removal stage). In short, the sequential pH adjustment method is able to recover and concentrate the metallic anions from the flocculated PSAs, and then recover the removal agent for recycling into the process with little deterioration of removal ability.